Allel-specific read counts for sprat population samples used in "Limited parallelism in genetic adaptation to brackish water bodies in European sprat and Atlantic herring" - Pettersson, Mats; Quintela, María; Besnier, François; Deng, Qiaoling; Berg, Florian; Kvamme, Cecilie; Bekkevold, Dorte; Mosbech, Mai-Britt; Bunikis, Ignas; Lille-Langøy, Roger; Leonori, Iole; Wallberg, Andreas; et al. (Uppsala University, 2024)
"Sprat_DeDup_v2_HiC.fasta.gz" contians the draft genome used in the study, in FASTA format. It is the version upon the SNPs (single nucleotide polymorphisms) described have been called.

"Sprat_pool_AD_DeDup_v2_PASS.txt.gz" contains tab-separated allele counts, as output using the "--counts" option in vcftools, from pool re-sequencting of the samples used in the study. Please see the corresponding supplementary information for sample codes etc. These counts underly the frequencies used throughout the study.
Keywords: Biological adaptation; Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Biological Sciences; Biologi